Comprehensive Assessment of Medicinal Plants for Their Antidiabetic Properties: Connecting In Vivo and In Vitro Evaluations with Advanced Computational Analyses, Encompassing ADMET Prediction, Molecular Docking, and Molecular Dynamics Simulation. - GOUNNI Ahlem; TEREA Joutheima Malik; KADI Maroua (Université of Eloued, 2024)
Diabetes is a group of metabolic diseases characterized by chronic hyperglycemia caused by an imbalance in the secretion. Insulin or its effect, or both disorders associated with serious disease complications associated with the ineffectiveness of the molecules of products used in its treatment. This prompted the WHO to use traditional medicine as an alternative solution. The induction of diabetes in the mouse model was achieved by injecting a fresh solution of aloxane intraperitoneum, and after a treatment period of 20 UMA, where weight and blood sugar were used in the case of fasting to evaluate the effectiveness of the treatment. In comparison between the different groups (the witness group, the healthy group treated, the group with diabetes and the group with diabetes treated) the results were shown in the mice with diabetes that were treated with a low blood sugar. In the laboratory we relied on the characterization of essential oils by analysing the gas-mass spectrometer chromatography (GC/MS) and predicting in silico of the physical, chemical properties and the pharmacological and toxicity of Mp-Al compounds) (the four selected using servers: swissADME, admitSAR and Protox. The results showed that all of these compounds have drug-like properties. EOs studied significantly increased α-amylase inhibition (%) with a corresponding increase in EO concentration. The effective inhibitory concentration (IC50 value) in which 50% of α-amylase activity was inhibited by Ammudoucus leucotrichus and Mentha piperita essential oils was obtained to be 7.013 and 1.310 μg/ml respectively, indicating a strong potential for slowing starch digestion by inhibition of α-amylase. The results obtained by molecular docking confirm the results in the laboratory; they have negative values ΔG, which reflects the good convergence of bonds with the biological target the anti-diabetic effectiveness of these oils and makes it possible to be considered antidiabetic drugs in the future.
Keywords: Mentha piperita; Ammudaucus leucotrichus; diabetes; swissADME; Alox